Perlindungan Hukum Pasien Dalam Keadaan Gawat Darurat : (Studi Di RSUD Dr. R. Soedjono Selong Lombok Timur) - Ghazwan Aqrabin Faqih; H. Arba Arba (Private Law, 2022)
The puppse The purpose of this study was to determine the regulation of the legal relationship between patients in an emergency situation and the hospital and the factors that hindered the Regional General Hospital Dr. R Soedjono Selong in providing emergency services to patients. This research is an empirical legal research using a statutory approach, a conceptual approach, and a sociological approach. The results of this study are the regulations governing Law No.36 of 2009 concerning Health, Law No.44 of 2009 concerningHospitals, Decree of the Minister of Health No.129/Menkes/SK//II/2008 concerning Minimum Service Standards for Homes. and Decree of the Minister of Health No. 865/Menkes/SK/IX/2009 concerning Hospital Emergency Installation Standards, as well as factors that hinder the Dr.R Soedjono Selong Regional General Hospital in providing emergency services to patients consisting of internal hospital factors. namely the lack of quality human resources, incomplete equipment, less bureaucracy to facilitate services and external factors from patients who do not know about their rights and obligations and patients know about triage / patient emergency level.